AUDIT QUALITY, AUDIT COMMITTEE, INSTITUTIONAL OWNERSHIP AND INDEPENDENT DIRECTOR ON EARNING MANAGEMENT - Ni Putu Desy Cristiana Yanthi; Dudi Pratomo; Kurnia Kurnia (JRAK, 2021)
This study aims to analyze audit quality, audit committees, institutional ownership and independent director on earnings management at manufacturing companies listed on the Indonesia Stock Exchange in 2012-2016. The sampling method use purposive sampling for 5 years so its obtained 160 observation data samples. The results in this study indicate that earnings management that occur is the type of income decreasing. Simultaneously audit quality, audit committee, institutional ownership and independent directors significantly influence on income decreasing. Partially, audit quality and independent director variables have a negative effect on income decreasing. While audit committee independence has a positive effect on income decreasing. Furthermore, audit quality, audit committees, and institutional ownership have no effect on earning management type income decreasing.